Pengaruh Metode Pembelajaran Drill terhadap Peningkatan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 2 Muara Aman - Zamratul Aini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Background: Mathematics is a very important subject to study. Mathematics lessons include the development and use of concepts such as numbers, formulas, geometry, and algebra to understand and explain phenomena in various contexts. To improve the quality of students' mathematics learning, it is necessary to develop material through a learning method which is expected to improve students' abilities in solving mathematical problems. Method: The research design is